2022
DOI: 10.1007/s44212-022-00019-9
|View full text |Cite
|
Sign up to set email alerts
|

Spatial-temporal differences of COVID-19 vaccinations in the U.S.

Abstract: Although the disparities in COVID-19 outcomes have been proved, they have not been explicitly associated with COVID-19 full vaccinations. This paper examines the spatial and temporal patterns of the county-level COVID-19 case rates, fatality rates, and full vaccination rates in the United States from December 24, 2020 through September 30, 2021. Statistical and geospatial analyses show clear temporal and spatial patterns of the progression of COVID-19 outcomes and vaccinations. In the relationship between two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Factors- occupation and language, policies and liquor stores, asthma, environmental hazards, and mental health centers became more significant in 2021. This emphasized the higher infection rates among healthcare-related workers and the White population, locations with short-term COVID-19 mitigation measures, and the significant side effects of alcohol and air pollution [ 25 ]. In 2022, as of June 30, Factor 3-Healthcare providers became positively significant, suggesting more exposure contacts in sufficient healthcare areas.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors- occupation and language, policies and liquor stores, asthma, environmental hazards, and mental health centers became more significant in 2021. This emphasized the higher infection rates among healthcare-related workers and the White population, locations with short-term COVID-19 mitigation measures, and the significant side effects of alcohol and air pollution [ 25 ]. In 2022, as of June 30, Factor 3-Healthcare providers became positively significant, suggesting more exposure contacts in sufficient healthcare areas.…”
Section: Resultsmentioning
confidence: 99%
“…Political party affiliation influences COVID-19 exposure and vaccination [ 25 ]. Studies showed that the COVID-19 pandemic has killed more Republican voters than Democratic voters since more Republicans opposed public health measures such as mask mandates and vaccination requirements [ 26 ].…”
Section: Nonstationarity and Health Disparitymentioning
confidence: 99%